ANALISIS PENDAPAT BUSTANUL ARIFIN DALAM PEMBAHARUAN HUKUM ISLAM DI INDONESIA - Hendrawati, Islamiyati Dewi (Diponegoro Private Law Review, 2018)
Islamic law in Indonesia is often not presented as objective, rational and scientific law, because it is based on the truth of the belief, and is not lawful. This paper analyzes Bustanul Arifin's thoughts on the basic idea of Islamic legal institutionalization. Urgency writing can explain the role of Islamic law and its development in the realm of the national legal system in Indonesia. According to Bustanul Arifin Islamic law needs to be institutionalized through the Religious Courts to solve the case of Muslims through legal channels. KHI President Instruction No. 1/1991 is the state school of thought to serve as the legal basis for judges in establishing cases. This idea inspired the state to establish legislation as problem solving in solving the problem of Islamic law. Key Word: Bustanul Arifin, Renewal, Islamic Law.